Osteochondral transplantation using autografts from the upper tibio-fibular joint for the treatment of knee cartilage lesions - Espregueira-Mendes, J (2012)
PURPOSE: Treatment of large cartilage lesions of the knee in weight-bearing areas is still a controversy and challenging topic. Autologous osteochondral mosaicplasty has proven to be a valid option for treatment but donor site morbidity with most frequently used autografts remains a source of concern. This study aims to assess clinical results and safety profile of autologous osteochondral graft from the upper tibio-fibular joint applied to reconstruct symptomatic osteochondral lesions of the knee. METHODS: Thirty-one patients (22 men and 9 women) with grade 4 cartilage lesions in the knee were operated by mosaicplasty technique using autologous osteochondral graft from the upper tibio-fibular joint, between 1998 and 2006. Clinical assessment included visual analog scale (VAS) for pain and Lysholm score. All patients were evaluated by MRI pre- and post-operatively regarding joint congruency as good, fair (inferior to 1 mm incongruence), and poor (incongruence higher than 1 mm registered in any frame). Donor zone status was evaluated according to specific protocol considering upper tibio-fibular joint instability, pain, neurological complications, lateral collateral ligament insufficiency, or ankle complaints. RESULTS: Mean age at surgery was 30.1 years (SD 12.2). In respect to lesion sites, 22 were located in weight-bearing area of medial femoral condyle, 7 in lateral femoral condyle, 1 in trochlea, and 1 in patella. Mean follow-up was 110.1 months (SD 23.2). Mean area of lesion was 3.3 cm2 (SD 1.7), and a variable number of cylinders were used, mean 2.5 (SD 1.3). Mean VAS score improved from 47.1 (SD 10.1) to 20.0 (SD 11.5); p = 0.00. Similarly, mean Lysholm score increased from 45.7 (SD 4.5) to 85.3 (SD 7.0); p = 0.00. The level of patient satisfaction was evaluated, and 28 patients declared to be satisfied/very satisfied and would do surgery again, while 3 declared as unsatisfied with the procedure and would not submit to surgery again. These three patients had lower clinical scores and kept complaints related to the original problem but unrelated to donor zone. MRI score significantly improved at 18-24 months comparing with pre-operative (p = 0.004). No radiographic or clinical complications related to donor zone with implication in activity were registered. CONCLUSIONS: This work corroborates that mosaicplasty technique using autologous osteochondral graft from the upper tibio-fibular joint is effective to treat osteochondral defects in the knee joint. No relevant complications related to donor zone were registered.